2020
DOI: 10.1136/bmjopen-2020-039279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a foot-ankle strengthening programme on clinical aspects and gait biomechanics in people with knee osteoarthritis: protocol for a randomised controlled trial

Abstract: IntroductionStudies have indicated that hip and knee muscle strengthening are effective in reducing pain, improving self-reported function and increasing lower limb strength, without, however, decreasing knee joint overload during gait in patients with knee osteoarthritis (KOA). Recent research has shown that strengthening the foot-ankle muscles improved function in diabetic patients and reduced patellofemoral pain. The aim of this paper is to investigate whether an 8-week therapeutic foot-ankle exercise progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Many patients with knee arthritis have unsatisfactory treatment results because they do not pay attention to foot and ankle function. Studies have shown that foot and ankle function have an impact on knee joint disease [ 39 ]. However, the impact of FMJC has not been defines.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with knee arthritis have unsatisfactory treatment results because they do not pay attention to foot and ankle function. Studies have shown that foot and ankle function have an impact on knee joint disease [ 39 ]. However, the impact of FMJC has not been defines.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated to estimate the equality between the therapeutic programme of muscular resistance, balance, and gait exercises with and without the use of low-cost flexible shoes and the treatment according to Osteoarthritis Research Society International Clinical Trials recommendations, based on the mean difference (pretreatment and post-treatment) in the WOMAC pain domain immediately after treatment. Previous studies evaluating therapeutic exercises for knee OA reported a post-treatment mean difference of 2.12 points between the intervention and control groups on the WOMAC pain subscale 44. Thus, based on an average intergroup difference of 2.12 points and assuming an SD of 3.3 points, we calculated a total of 36 participants (12 per group) required to provide an 80% power at a significance level of 5% and detect this difference, assuming a 10% dropout rate after randomisation.…”
Section: Methods and Analysismentioning
confidence: 96%
“…Previous studies evaluating therapeutic exercises for knee OA reported a post-treatment mean difference of 2.12 points between the intervention and control groups on the WOMAC pain subscale. 44 Thus, based on an average intergroup difference of 2.12 points and assuming an SD of 3.3 points, we calculated a total of 36 participants (12 per group) required to provide an 80% power at a significance level of 5% and detect this difference, assuming a 10% dropout rate after randomisation.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations